Counselling on breastfeeding during the puerperium by the Dentist: A review (Research, Society and Development, 2021)
This study is a review of the literature addressing the main topics on breastfeeding. The search for available studies took place in the electronic databases, based on previously selected keywords. It was possible to observe that breastfeeding has many advantages for the development and growth of the baby, in addition to numerous benefits for their mothers. This review addresses the proper breastfeeding technique and the guidelines that the dentist must follow to avoid early weaning. The mothers' lack of information makes themselves to feel insecure when talking about breastfeeding their child, the dentist must be able to welcome and support since the prenatal period until the time it is necessary. It is extremely important to provide guidance on breastfeeding in times of COVID-19, the professional must ensure for mothers that the benefits of exclusive breastfeeding up to 6 months of age are fundamental for the newborn, and that even if the mother is infected by the virus, it is still advisable to breastfeed her child.